Complete mitochondrial genome of Scincella modesta (Squamata: Scincidae) - Lian Chen; Youfu Lin; Ying Lin; Yaping Hu; Qi Xiao; Xu Zhou; Yan Liu; Hong Li (Mitochondrial DNA. Part B. Resources, 2020)
The first complete mitochondrial genome sequence was determined for an oviparous lizard, Scincella modesta (Scincella, Scincidae). The total length of the complete mitochondrial genome was 17,511 bp, encodes 13 protein-coding genes, 22 tRNAs, 2 rRNA genes, and 2 non-coding regions. The overall base composition of S. modesta is A: 31.9%, T: 27.2%, G: 14.5%, and C: 26.5%. Most of the S. modesta mitochondrial genes are encoded on the H-strand except for the ND6 gene and eight tRNA genes, which are encoded on the L-strand. Mrbayes and ML tree based on 13 protein-coding genes indicated that S. vandenburghi is the sister group of the S. modesta within the genus Scincella. The complete mitogenome sequence of S. modesta provided fundamental data for resolving phylogenetic and genetic problems related to genus Scincella.